Mitigation of carbide lime waste and CO2 gas emission from acetylene gas industry: feasible technique of high-grade PCC production - Salleh, Emee; Othman, Rohaya; Mohd Sabri, Siti Noorzida (Thai Geoscience Journal, 2022)
The global acetylene gas market is currently witnessing stable growth. Owing to its high flame- -temperature properties, acetylene gas is extensively used for numerous metalworking applications including oxy-acetylene cutting, heat treating, soldering, brazing and welding. Acetylene gas is a colourless combustible gas that is produced through the combination of calcium carbonate (CaCO3) and water. However, the gas manufacturing results in a production of carbide lime as a by-product that is classified as a scheduled waste in Malaysia under Environmental Quality Act: EQA 1974 (SW 427). In addition to the abundant carbide lime waste, the acetylene manufacturing also causes an increase in carbon dioxide (CO2) gas emission that trap heat in the atmosphere. This phenomenon has become a crucial environmental concern as the rise of CO2 gas emission leads to global warming. In mitigating the accumulative wastes, this current work was performed by revolutionising the carbide lime waste that is rich in calcium hydroxide (Ca(OH)2) of 25 to 30% and CO2 gas waste as a main precursor of carbonate (CO3 2−) ions in producing high- -grade precipitated calcium carbonate (PCC). The high-grade PCC was produced using these industrial wastes as primary starting materials via a feasible carbonation technique. In increasing the PCC yield, the production of PCC was initiated via forming an ionic solution by extracting Ca2+ ions from carbide lime waste using a promoter agent. The current outcome signified that 20 g of high-grade PCC with a purity of 98% was produced for every 1 litre of ionic solution. Interestingly, miscellaneous functional morphologies namely rhombohedral and spherical structures of PCC were formed, attributable to various processing parameters. Effectively, the PCC production was completed within less than 10 minutes per litre of ionic solution which significantly offered a fast-rate process. The conducted feasible carbonation technique provides high potential in converting the harmful industrial wastes to profitable products. Via this technique, the production of high-grade PCC as a main product with zero waste, not only reduces the waste management cost but also increases the industrial profits. Remarkably, the recycling of abundant carbide lime waste and CO2 gas usage in producing high-grade-high-profit PCC results in zero waste production, and thus may help in preserving environmental sustainability.